Manajemen Strategi untuk Meningkatkan Tingkat Outcome di SMK Negeri 14 Garut - Ropa Mustopa Nurrahman; Purwadhi; Yani Restiani Widjaja (Jurnal Masharif Al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The partnership between vocational high schools and the industrial sector serves as a crucial strategy in enhancing graduates' competitiveness. However, SMK Negeri 14 Garut faces challenges such as a skills gap between graduates and industry needs, limited collaboration with local industries, and a lack of parental support for labor mobility. This study aims to analyze the implementation of strategic management in the partnership between SMK Negeri 14 Garut and the industrial sector to improve graduates’ employability. This research employs a qualitative approach, utilizing in- depth interviews, observations, and document analysis. The study’s informants include the school principal, vice principal for industrial relations, vocational program teachers, industry representatives, internship students, and administrative staff. The data were analyzed descriptively to identify internal and external factors affecting the effectiveness of school-industry partnerships. The findings indicate that SMK Negeri 14 Garut has implemented partnership strategies through curriculum alignment with industry standards, teacher training, and the enhancement of internship programs. Internal supporting factors include an industry-based curriculum and the presence of a Special Job Market Bureau (BKK), while key challenges involve limited practical facilities and insufficient collaboration with local industries. External factors influencing the partnership include government policies and advancements in educational technology. This study contributes by proposing adaptive strategies, such as expanding partnerships with local industries and developing entrepreneurship programs, to enhance partnership effectiveness and increase graduates' employment opportunities.